2016
DOI: 10.1111/resp.12794
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal origins of reduced lung function‐but not asthma?

Abstract: http://onlinelibrary.wiley.com/doi/10.1111/resp.12718/abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The apparently inconsistent findings between cohorts for associations between fetal size and symptoms may reflect differences in response bias and differences in methodologies, including definitions used and age at assessment. However, there is also a recognised disconnect between reduced lung function and asthma symptoms, and thus a relationship may not be apparent in every population [18].…”
Section: Introductionmentioning
confidence: 99%
“…The apparently inconsistent findings between cohorts for associations between fetal size and symptoms may reflect differences in response bias and differences in methodologies, including definitions used and age at assessment. However, there is also a recognised disconnect between reduced lung function and asthma symptoms, and thus a relationship may not be apparent in every population [18].…”
Section: Introductionmentioning
confidence: 99%
“…77 The intense interest in the developmental origins of respiratory physiology and disease was also highlighted in an interesting paper from Popovic et al 78 using an internet-based birth cohort that found that size and weight gain velocity but not age at peak weight velocity were independently associated with an increased risk of wheezing in the first 18 months of life. Nice summaries and discussions of these findings are found in editorials by Duijts 79 and Turner 80 who reflected that there are early infant origins of wheeze and asthma symptoms and even earlier foetal origins of lung function with other factors including atopy that also likely impact. Of particular note it seems that reduced lung function per se predisposes to, but does not appear to, cause respiratory symptoms and asthma.…”
Section: Claire E Wainwrightmentioning
confidence: 99%
“…Different antenatal exposures, mainly maternal smoking, but also alcohol intake and air pollutants, 5–8 as well as hypertensive pregnancy complications, 5 have been linked to impaired lung function in children. Reduced fetal size and growth have also been associated with lower infant lung function, 9–12 whereas less consistent associations were observed with symptoms related to asthma in infancy and childhood 9–13 . A newly published study showed an inverse association between mid‐pregnancy thoracic circumference (TC), adjusted for femur length as a TC/femur length ratio, and infant lung function 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Reduced fetal size and growth have also been associated with lower infant lung function, [9][10][11][12] whereas less consistent associations were observed with symptoms related to asthma in infancy and childhood. [9][10][11][12][13] A newly published study showed an inverse association between mid-pregnancy thoracic circumference (TC), adjusted for femur length as a TC/femur length ratio, and infant lung function. 14 Ultrasound measures related to fetal lung size, such as lung volume (LV) or lung area, as well as TC, have a predictive value for neonatal respiratory outcome and survival in certain pathological conditions such as diaphragmatic hernia and skeletal dysplasia.…”
Section: Introductionmentioning
confidence: 99%